Smuggling Crimes as a Threat to the National Economy - Mohamed Djagham , Abdelhalim Benmechri , Farid Allouache (Migration Letters, 2024)
Smuggling is considered one of the most dangerous economic crimes and the most damaging to the national economy. Therefore, comparative legislations, despite their different economic policy orientations, have consistently criminalized and punished this act. The Algerian legislator has not deviated from this pattern, and smuggling has remained a crime regulated by the customs law since its issuance in 1979 until the issuance of Order 05-06, which includes combating smuggling. However, despite being a specialized Algerian law, it did not deviate in its definition of smuggling crimes from the effective legislations, especially the customs law, while adding forms that deviate from the commonly understood meaning in customs law for smuggling, without nullifying the provisions of the latter, this duplication in the definition has cast its shadow on the general meaning of this crime, prompting us to present this research paper that attempts to reveal the ability of the effective legal texts to achieve the required legislative sufficiency to clarify the nature of smuggling crimes.